Síndrome de Reye congénito asociado a varicela materna (2014)
Introduction: Reye’s syndrome is an acute encephalopathy associated with fatty degeneration of the liver that usually is preceded by a respiratory infection or chickenpox and is highly prevalent in children under 6 years old. Objective: to report a clinical case of congenital Reye’s syndrome associated with varicella infection acquired from the mother. Case report: we describe the autopsy findings with the respective clinicopathological correlation of a male newborn of 37 weeks of gestation, son of mother with active varicella from 4 days before birth, who presented sudden paleness, bradycardia and apnea. Results: histopathologic examination found in the cytoplasm of hepatocytes and renal tubules a vacuolar commitment that corresponds to fat. The brain showed severe edema without perivascular or meningeal inflammation. Discussion and conclusion: it corresponds a case of congenital Reye’s syndrome associated with varicella infection in pregnancy, who finished clinically as sudden death. This could be the first published case of congenital Reye’s syndrome associated with varicella infection in pregnancy. MÉD.UIS. 2014;27(3):113-121.